Momentum flux, energy flux and pressure drag associated with mountain wave across western ghat - DUTTA, SOMENATH (MAUSAM, 2001)
An attempt has been made to parameterize the wave momentum flux wave energy flux and pressure drag associated with mountain wave across the Mumbai-Pune section of western ghat mountain in India. A two dimensional frictionless, adiabatic, hydrostatic, Boussinesq flow with constant basic flow (U) and constant Brunt Vaisala frequency (N) across a mesoscale mountain with infinite extension in the Cross wind direction, has been considered here. It has been shown that for a vertically propagating (or decaying) waves the wave momentum flux is downward (or upward) and the wave energy flux is upward (or downward). It has also been shown that both the fluxes are independent of the half width of the bell shaped part of the western ghat. The analytically derived formula have been used to compute the pressure drag and to find out the vertical profile of wave momentum flux and wave energy flux for different cases of mountain wave across western ghat, as reported by earlier workers.